MEDIATING ROLE OF DEPRESSION AND ANXIETY ON SOMATIC COMPLAINTS IN GEORGIAN SERVANTS WITH POST TRAUMATIC STRESS DISORDER - Sikharulidze, Giorgi; Sordia, Mariam; Vermetten , Eric (International Journal of Scientific Research and Management (IJSRM), 2023)
Background and Objectives: The relationship between Post Traumatic Stress Disorder (PTSD) and somatic symptoms and the role of comorbid depression and anxiety has been demonstrated in many studies. The following research explores to what extent depression and anxiety influence the relationship between PTSD and somatic complaints in Georgian peacekeepers.Design and Methods: PTSD Checklist (PCL-5) for The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and Patient Health Questionnaire (PHQ) was used to collect data in the sample of 75 veterans examined after a 6-month deployment. Two types of parallel mediation model 4 of the SPSS PROCESS macro were used to check different and also joint influences of depression and anxiety on the indirect effect of PTSD on somatic complaints. Results: When probable mediators were analyzed separately, there was a significant indirect effect of PTSD on somatic complaints: through depression 0.21, 95% CI [0.13, 0.28], and through anxiety 0.13, 95% CI [0.06, 0.21]. After placing both mediators in a parallel model, only depression maintained statistical significance: 0.18, 95% CI [0.09, 0.28]. The ratio of indirect to total effect was 0.66, 95% CI [0.59, 0.75].Conclusions: The primary finding is that the relationship between PTSD and somatic complaints may be mainly accounted for underlying symptoms of depression rather than anxiety, highlighting the importance of targeting depression symptoms when diagnosing and treating comorbid PTSD and somatic complaints. These new results may affect both the management and treatment of PTSD as they acknowledge the importance of anxiety and depression symptoms in somatic complaints.